The Comparison Between Principals Management Styles In Schools, General Public sample, Nonprofit, Gifted High school Teachers' views of downtown Tehran - علیرضا جوان بخت; محمد یمنی دوزی سرخابی; Abasalt Khorasani (Allameh Tabataba'i University Press, 2016)
The present study compared management styles in types of boy regular, public sample, non-profit and gifted high schools based on view of teachers in Tehran.This research is functional in terms of goal and descriptive - survey in terms of data collection method. . The statistical population included all secondary school teachers (regular, non-profit, gifted and sample public) in Tehran boys in the 2012-2013 school years. According to the Morgan Table, 165 public high school teachers, 201 non-profit high school teachers, 28 gifted high school teachers and 73 public sample were selected as a sample. The Clustered and Classified sampling methods were used in this study and the research instrument was questionnaire that its validity and reliability were acceptable. For data analysis, descriptive statistics (such as diagrams, frequency, percentage, mean) and inferential statistics(one-way analysis of variance test, LSD post hoc test, one sample T test and chi-square test were used. in general, the following results were obtained: 1-There are Significant difference in the usage of relationship-oriented and task-oriented management styles in the public, non-profit, public sample and gifted high schools. 2-There is no significant relationship between management styles and the type of schools. 3-there are no significant differences between dominant styles of management in the public, public sample , gifted Schools but there are significant differences in the non-profit schools so that the average relationship-oriented style is more than task-oriented style.